POTRET BALIK DUNIA POLITIK ISLAM - Hasbi Sidik (Millah: Journal of Religious Studies, 2013)
Islam is universal religion. An s Syahrur said that: from the end of nineteenth century until now, a popular slogan has been heard: 'Islam is the solution". This means that, Islam is no only guide about religion but also politic. Politic discourse is current moment rise the discourse of other Islam thought, like theology, kalam and tasawuf. The history proved that politic is the first problem which is to be considered ly moslem, is about politic success. Also this phenomenon to be based on rise thought discourse on relation between nation and religion in the moslem world. In the classic era, there are many percevective about police in Islam. Like Sunni, Shi’a, Khawarij and the another madhhab in Islam. A l l of theme is deperent each other. The main idea in this writing, relation between nation and religion, how is Islam viewing development? So to focus this writing The first histories of politic in word of Islam, The second, typology and character politic and then, it is discoursed about how is the Islam nation position in the perspective of Quran texts. This writing dames that the Muslims thought agreed that Islam and moslem need nation. The end, Islam wants to be given shape to social politic society of Islam which high respect fairness or social justice, and humanity values. The social order of society of socio-politics had been historic in Medina, when the Prophet Muhammad’s leadership. This condition, shows that Islam is for situation from the book (al-Qur’an) hoping. This article will analyze about this problem.